Media pluralism and the future of journalism - Masip, Pere (Anuario ThinkEPI, 2018)
Circulation figures for print newspapers in Spain were historically low in 2017. However, digital media continues to grow, although only a handful of sites are financially profitable. The search for a profitable business model has superseded what is vital in journalism: quality information. In an attempt to identify the causes that have led to the current situation, this article describes the problems of pluralism in the Spanish media system. The lack of political independence and editorial autonomy are some of the problems identified. Media that are economically sustainable and politically independent are necessary for a truly democratic society.